Early predictors of summative assessment performance in general practice post-graduate training: A retrospective cohort study. (2nd November 2018) - Stewart, Rebecca; Cooling, Nick; Emblen, Graham; Turnock, Allison; Tapley, Amanda; Holliday, Elizabeth; Ball, Jean; Juckel, Jennifer; Magin, Parker
Abstract: Background: Success in summative general practice (GP) training assessments is one indicator of competence for practice. Early-training factors predictive of outcomes would facilitate targeted interventions aimed at preventing candidate failures. Methods: We undertook a retrospective cohort study of Australian GP trainees in two training organizations over five years. Associations of pre-training and early-training predictors with summative examination scores in an Applied Knowledge Test (AKT), Key Features Paper (KFP), and Objective Structured Clinical Examination (OSCE), plus failure on any one of these, were tested via univariate and multivariable regression. Predictors were program-entry selection-score decile, pre-training-commencement multiple choice assessment (MCQA), direct observation of practice performance, and clinical supervisor reports. Results: On univariate analyses, selection decile and MCQA were associated with all outcomes except AKT. There were no associations of other predictors with any outcomes. On multivariable analysis, selection decile and MCQA performance were predictive of OSCE performance. MCQA performance was also predictive of KFP performance. On multivariable analysis, no predictors were associated with AKT performance or failing any examination. Conclusions: Selection decile and pre-commencement MCQA performance were predictive of performance in some summative assessments. These findings could inform selection policies and targeted early interventions for trainees at most risk for exam failure.